The Home Economics of E-Money: Velocity, Cash Management, and Discount Rates of M-Pesa Users - Mbiti, Isaac; Weil, David N (American Economic Review, 2013)
We study the mobile phone-based money transfer system in Kenya. Based on aggregate data, we estimate that the velocity with which units of e-money are transferred among users is approximately four times per month, and that the average number of transfers undergone by a unit of e-money between its creation and destruction is approximately one. Most M-Pesa transactions are made by frequent users. Examination of data on withdrawals shows a high frequency of small withdrawals and no response to “notches” in the price schedule, indicating that many users seem to have high implicit discount rates.